Impacto da Idade Materna Avançada na Morbilidade Neonatal: Revisão Sistemática - Maria Inês Bastos Rodrigues (2022)
Objective: This systematic review aimed to understand the impact of advanced maternal age (AMA) on the neonatal morbidity, based on the available scientific evidence. Methods: A systematic search was conducted on November 22, 2021, using the PubMed and Scopus databases to identify studies that compared the morbidity of neonates delivered to AMA mothers with that of neonates delivered to non-AMA mothers. Results: Sixteen studies that evaluated the effect of AMA on the neonatal morbidity were included in this review. Nine of these studies found some association between AMA and increased neonatal morbidity (with two of them only reporting an increase in asymptomatic hypoglycemia), six found no association between AMA and neonatal morbidity and one study found a decrease in morbidity in preterm neonates. The studies that found an increase in overall neonatal morbidity with AMA considered older ages for the definition of AMA, particularly ≥40 and ≥45 years. Conclusion: With the current evidence, it's not possible to define a clear effect of AMA on the neonatal morbidity of the delivered neonates. More studies focusing on the neonatal outcomes of AMA pregnancies are needed to better understand this topic.